Psychological Determinants and Consequences of COVID-19 Anxiety: A Web-Based Study in Iran - Reza Shabahang; Mara S. Aruguete; Sajjad Rezaei; Lynn E. McCutcheon (Health Psychology Research)
Pandemic illnesses such as COVID-19 can provoke negative emotions, including anxiety and depression, in addition to compulsive behaviors. Clarifying the psychosocial antecedents and consequences of COVID-19 anxiety can inform successful psychological support and treatment. This study investigated psychological predictors and consequences of COVID-19 anxiety during the outbreak of COVID-19 in Iran. University students (N = 398) completed a web-based survey measuring COVID-19 anxiety, general health anxiety, uncertainty intolerance, interpersonal trust, depression, and COVID-19-related panic shopping. The participants also responded to two additional questions: "Do you personally know of anyone who was suspected of having been infected with COVID-19?" and "Did you get sick in the past year?” Exploratory factor analysis, confirmatory factor analysis, Pearson correlation, multiple regression analysis, multivariate regression analysis, and 2 × 2 factorial ANOVA were used to analyze data. Health anxiety, uncertainty intolerance, and interpersonal trust were significantly associated with COVID-19 anxiety. COVID-19 anxiety was a significant predictor of depression and panic shopping. Participants who knew someone with COVID-19 and those who reported being sick in the past year experienced more COVID-19 anxiety. COVID-19 anxiety appears to be more severe among people with a low tolerance for uncertainty and low interpersonal trust. Understanding these risk factors can inform individualized therapeutic approaches to address the maladaptive outcomes of depression and false safety behaviors, such as panic buying.